Arrested development and philosophy they've made a huge mistake - Phillips, Kristopher G., 1981-; Wisnewski, Jeremy (Blackwell philosophy and popculture series, 2012)
"A smart philosophical look at the cult hit television show, Arrested Development. Arrested Development earned six Emmy awards, a Golden Globe award, critical acclaim, and a loyal cult following-and then it was canceled. Fortunately, this book steps into the void left by the show's premature demise by exploring the fascinating philosophical issues at the heart of the quirky Bluths and their comic exploits. Whether it's reflecting on Gob's self-deception or digging into Tobias's double entendres, you'll watch your favorite scenes and episodes of the show in a whole new way. Takes an entertaining look at the philosophical ideas and tensions in the show's plots and themes. Gives you new insights about the Bluth family and other characters: Is George Michael's crush on his cousin unnatural? Is it immoral for Lindsay to lie about stealing clothes to hide the fact that she has a job? Are the pictures really of bunkers or balls? Lets you sound super-smart as you rattle off the names of great philosophers like Sartre and Aristotle to explain key characters and episodes of the show. Packed with thought-provoking insights, Arrested Development and Philosophy is essential reading for anyone who wants to know more about their late, lamented TV show. And it'll keep you entertained until the long-awaited Arrested Development movie finally comes out. (Whenever that is.)"--